Keterampilan Menulis Teks Percakapan Bahasa Bugis Siswa Kelas VIII SMP Negeri 3 Soppeng: Writing Skills of Bugis Language Conversation Texts of Class VIII Students of SMP Negeri 3 Soppeng - Wildana, Wildana; Syamsudduha , Syamsudduha; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2025)
This research is a quantitative descriptive study which aims to describe the skills of writing conversational texts in the Bugis language of class VIII students at SMP Negeri 3 Soppeng. The population in this study was all students in class VIII of SMP Negeri 3 Soppeng, totaling 101 students divided into four classes. The sample determined was 60 students from four classes using proportional random sampling technique. The research data was obtained by giving a conversation writing test. The data analysis technique used in this research is descriptive statistical techniques. Based on the results of data analysis, there were 58 samples that got a score of ≥75 with a percentage of 97%, while there were 2 samples that got a score of <75 with a percentage of 3%. It can be concluded that class VIII students at SMP Negeri 3 Soppeng are categorized as skilled in writing Bugis language conversational texts, seen from the percentage of students who obtained a score of ≥75 as many as 58 people with a percentage (97%) in the skilled category achieving the criteria for completing the set learning objectives, namely 75% got a score of 75.